Penerapan Teknik Drum Miking Pada Program Music Show Sound Session - Baharuddin, Nabhan; Sunarsa, Sunarsa; Utari, Tituk (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
Music show program is one of the entertainment programs that reviews music. In this program presents a musical performance of a person (Solo) or several people (Group) and talks with guest stars with the aim of meeting the needs of the audience. In this case, the author found several music show works that have not applied miking techniques and stereo miking techniques to the drum instrument, so that the microphone cannot capture the sound produced by the sound source optimally. So the author uses the miking and stereo miking technique methods in the music show work Sound Session. The aim is to produce a music show program Sound Session by applying miking techniques including selection techniques, microphone placement and applying stereo miking techniques. From the results of the analysis, after applying the selection technique, microphone placement and stereo miking techniques to the drum instrument, the goal of the music program is achieved which has harmonious and harmonious audio quality results, so that the information conveyed can be received well and can be enjoyed by the audience.